1999
DOI: 10.1097/00005392-199904020-00155
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Growth Rate Determined From Mri Data

Abstract: Men with prostatic enlargement are at highest risk of developing symptomatic lower urinary tract symptoms (LUTS) and related outcomes, such as acute urinary retention. The study of prostatic growth rate can identify the age range at which prostate growth peaks. Evaluation of the natural course of prostate growth requires repeated intraindividual volume measurements at time intervals sufficient to document growth. Our objective was to examine age‐stratified prostate growth rates from men taking part in a longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 0 publications
5
29
0
1
Order By: Relevance
“…In this study, the rate of growth was dependent on baseline prostate volume; the larger the prostate at baseline, the greater the percentage growth every year thereafter. Similar findings also were reported in men participating in the Baltimore Longitudinal Study of Aging [11,41]. Thus, although prostate volume is known to correlate poorly with symptoms and urinary flow at any given time, large prostate volume portends future clinical deterioration.…”
Section: Progressive Nature Of Benign Prostatic Hyperplasiasupporting
confidence: 76%
“…In this study, the rate of growth was dependent on baseline prostate volume; the larger the prostate at baseline, the greater the percentage growth every year thereafter. Similar findings also were reported in men participating in the Baltimore Longitudinal Study of Aging [11,41]. Thus, although prostate volume is known to correlate poorly with symptoms and urinary flow at any given time, large prostate volume portends future clinical deterioration.…”
Section: Progressive Nature Of Benign Prostatic Hyperplasiasupporting
confidence: 76%
“…Regarding the prostate, all groups showed increases in prostate volume that were greater than those observed previously in prospective studies of older men (31,32). The change in ultrasound equipment between baseline and the end of the study may have contributed to the seemingly larger-than-expected magnitude of volume change between baseline and end-of-study.…”
Section: Discussionmentioning
confidence: 47%
“…6 Using MRI instead our research group previously reported on age related prostate volume changes in 64 community men from the Baltimore Longitudinal Study of Aging. 7 In these men the overall prostate growth rate was 2.36 cc per year. In this study we expand on these findings and further examine longitudinal changes in prostate volume in a larger population of community men from the BLSA.…”
mentioning
confidence: 85%
“…Since then approximately 1,806 males have enrolled, primarily residents of Maryland or Washington, D. C. As part of the study protocol participants undergo a comprehensive medical, physical and neuropsychological evaluation every 2 years as previously described. 7,8 All BLSA subjects provided informed consent, and the study protocol was approved by the institutional review boards of MedStar and the Johns Hopkins Medical Institutions (Baltimore, Maryland).…”
Section: Methodsmentioning
confidence: 99%